Examining Individual and Aggregate Correlates of Police Killings of People with Mental Illness: A Special Gaze at Race and Ethnicity - Prince, Krishanna J. (Homicide studies, 2023)
This study assesses the influences of race and ethnicity on the presence of resistant behavior during deadly police contacts with people experiencing mental illness. Drawing upon information mainly from the Mapping Police Violence Database, regression analysis showed that race/ethnicity is not a consistent predictor of resistance among people with mental illness. Hispanics with mental illness were less likely than White counterparts to attack the police before being killed. Counties with a higher percentage of the Black population have a higher likelihood of people with mental illness attacking the police.